2022
DOI: 10.3389/fped.2022.800300
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival Among Preterm Neonates Admitted to Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia

Abstract: BackgroundPre-maturity is the primary cause of neonatal mortality in the world. Although prematurity was the leading cause of neonatal mortality, the survival rate and its predictors may be varied from setting to setting and time to time due to different reasons. Therefore, this study aimed to assess the survival probability and predictors of mortality among preterm neonates at Felege Hiwot comprehensive specialized hospital.MethodsThis is a retrospective follow-up study that included 542 randomly selected pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
(67 reference statements)
0
7
2
Order By: Relevance
“…On the other hand, the finding of this study is lower than that of the studies conducted in Bahir Dar, Ethiopia16 and Ghana 25. Moreover, in this finding is the median survival time is lower than the study conducted in Tigray region of Ethiopia,26 Bahir Dar, Ethiopia 27…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, the finding of this study is lower than that of the studies conducted in Bahir Dar, Ethiopia16 and Ghana 25. Moreover, in this finding is the median survival time is lower than the study conducted in Tigray region of Ethiopia,26 Bahir Dar, Ethiopia 27…”
Section: Discussioncontrasting
confidence: 77%
“… 25 Moreover, in this finding is the median survival time is lower than the study conducted in Tigray region of Ethiopia, 26 Bahir Dar, Ethiopia. 27 …”
Section: Discussionmentioning
confidence: 99%
“…This might be possible because low birth weight preterm infants have low growth and immature organ development. This can increase complications and death (Belay et al, 2022). Therefore, birth weight of preterm infants with RDS could predict survival of preterm infants with RDS.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Table 2, all the selected studies were published between 2015 and 2023. Eight studies were conducted in Amhara, 13,14,18,[23][24][25][26][27] three studies were in the Oromia, 16,17,20 and two studies were in Southern nations nationalities and peoples region, 21,28 In Addis Ababa, there were two studies, 15,19 and one study was in Tigray region 22 of Ethiopia. However, in terms of study design, two studies were prospective cohorts, while 14 studies 13,14,[16][17][18][19][20][21][22][23][24]26,27 were retrospective cohorts.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…12 Generally, reports from studies done on preterm neonates treated at different health facilities in Ethiopia showed inconsistent preterm survival rates and its predictors. [13][14][15][22][23][24][25][26][27][28] Therefore, this study aimed to assess the pooled incidence of preterm mortality and its predictors among preterm neonates treated at different levels of health facilities in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%